Remembering, History, and Identity: The Sculpted Life of Benjamin Franklin - Mert Deniz (European Journal of American Studies)
History and memory are always in interaction as history is the craft of composing fragments of memory into an understandable narrative, so it serves as a medium of transferring memories between individuals, who thus achieve a form of self-definition. However, due to the specific nature of memory as well as the discipline of history’s own methods of reconstructing memory, the subjects of history are recreated over and over again in each artifact of history. The statues of Benjamin Franklin, honoring one of the most popularly acknowledged individuals in American history and social memory, perfectly exemplify the interrelation between history and memory.Benjamin Franklin, art history, social-cultural history, sculpture, remembering, memory, identity, narration